Case Report: Signal Transducer and Activator of Transcription 3 Gain-of-Function and Spectrin Deficiency: A Life-Threatening Case of Severe Hemolytic Anemia - Ciullini Mannurita, Sara; Goda, Rayan; Schiavo, Ebe; Coniglio, Maria Luisa; Azzali, Annachiara; Fotzi, Ilaria; Tondo, Annalisa; Tintori, Veronica; Frenos, Stefano; Sanvito, Maria Chiara; Vignoli, Marina; Luceri, Cristina; et al. (Frontiers in Immunology, 2021)
STAT3 gain-of-function (GOF) mutations can be responsible for an incomplete phenotype mainly characterized by hematological autoimmunity, even in the absence of other organ autoimmunity, growth impairment, or severe infections. We hereby report a case with an incomplete form of STAT3 GOF intensified by a concomitant hereditary hematological disease, which misleads the diagnosis. The patient presented with lymphadenopathy, splenomegaly, hypogammaglobulinemia, and severe autoimmune hemolytic anemia (AIHA) with critical complications, including stroke. A Primary Immune Regulatory Disorders (PIRD) was suspected, and molecular analysis revealed a de novo STAT3 gain-of-function mutation. The response to multiple immune suppressive treatments was ineffective, and further investigations revealed a spectrin deficiency. Ultimately, hematopoietic stem cell transplantation from a matched unrelated donor was able to cure the patient. Our case shows an atypical presentation of STAT3 GOF associated with hereditary spherocytosis, and how achievement of a good long-term outcome depends on a strict clinical and laboratory monitoring, as well as on prompt therapeutic intervention.